Collection Management in Sci-Tech Libraries, 1st edition - Mount, Ellis (Routledge, 2020)
This book, first published in 1989, covers all aspects of sci-tech collection management. It analyses the planning, careful use of budgets and wise selections required to build a suitable collection.